Wavelength dependent graphene oxide-based optical microfiber sensor for ammonia gas - Girei, Saad Hayatu; Alkhabet, Mohammed Majeed; Mustapha Kamil, Yasmin; Lim, Hong Ngee; Mahdi, Mohd Adzir; Yaacob, Mohd Hanif (MDPI, 2021)
Ammonia detection in ambient air is critical, given its implication on the environment and human health. In this work, an optical fiber tapered to a 20 µm diameter and coated with graphene oxide was developed for absorbance response monitoring of ammonia at visible (500–700 nm) and near-infrared wavelength regions (700–900 nm). The morphology, surface characteristics, and chemical composition of the graphene oxide samples were confirmed by a field emission scanning electron microscope, an atomic force microscope, X-ray diffraction, and an energy dispersion X-ray. The sensing performance of the graphene oxide-coated optical microfiber sensor towards ammonia at room temperature revealed better absorbance response at the near-infrared wavelength region compared to the visible region. The sensitivity, response and recovery times at the near-infrared wavelength region were 61.78 AU/%, 385 s, and 288 s, respectively. The sensitivity, response and recovery times at the visible wavelength region were 26.99 AU/%, 497 s, and 192 s, respectively. The selectivity of the sensor towards ammonia was affirmed with no response towards other gases.